Puberty contributes to adolescent development of fronto-striatal functional connectivity supporting inhibitory control. (December 2022) - Ojha, Amar; Parr, Ashley C.; Foran, William; Calabro, Finnegan J.; Luna, Beatriz
Abstract: Adolescence is defined by puberty and represents a period characterized by neural circuitry maturation (e.g., fronto-striatal systems) facilitating cognitive improvements. Though studies have characterized age-related changes, the extent to which puberty influences maturation of fronto-striatal networks is less known. Here, we combine two longitudinal datasets to characterize the role of puberty in the development of fronto-striatal resting-state functional connectivity (rsFC) and its relationship to inhibitory control in 106 10–18-year-olds. Beyond age effects, we found that puberty was related to decreases in rsFC between the caudate and the anterior vmPFC, rostral and ventral ACC, and v/dlPFC, as well as with rsFC increases between the dlPFC and nucleus accumbens (NAcc) across males and females. Stronger caudate rsFC with the dlPFC and vlPFC during early puberty was associated with worse inhibitory control and slower correct responses, respectively, whereas by late puberty, stronger vlPFC rsFC with the dorsal striatum was associated with faster correct responses. Taken together, our findings suggest that certain fronto-striatal connections are associated with pubertal maturation beyond age effects, which, in turn are related to inhibitory control. We discuss implications of puberty-related fronto-striatal maturation to further our understanding of pubertal effects related to adolescent cognitive and affective neurodevelopment.